Cross modal similarity learning with active queries. (March 2018) - Gao, Nengneng; Huang, Sheng-Jun; Yan, Yifan; Chen, Songcan
Highlights: A novel approach COSLAQ for cross modal similarity learning with active queries is proposed. Disagreement-based active query strategy explores the most valuable supervised information. Uncertainty of similarity learning model is utilized to avoid querying outliers and noises. Abstract: In real applications, data is usually collected from heterogeneous sources and represented with multiple modalities. To facilitate the analysis of such complex tasks, it is important to learn an effective similarity across different modalities. Existing similarity learning methods usually requires a large number of labeled training examples, leading to high labeling costs. In this paper, we propose a novel approach COSLAQ for active cross modal similarity learning, which actively queries the most important supervised information based on the disagreement among different intra-modal and inter-modal similarities. Furthermore, the closeness to decision boundary of similarity is utilized to avoid querying outliers and noises. Experiments on benchmark datasets demonstrate that the proposed method can reduce the labeling cost effectively.